A cutting-edge strategy for spinal cord injury treatment: resident cellular transdifferentiation - Fang, Yu-Ming; Chen, Wei-Can; Zheng, Wan-Jing; Yang, Yu-Shen; Zhang, Yan; Chen, Xin-Li; Pei, Meng-Qin; Lin, Shu; He, He-Fan (Frontiers in Cellular Neuroscience, 2023)
Spinal cord injury causes varying degrees of motor and sensory function loss. However, there are no effective treatments for spinal cord repair following an injury. Moreover, significant preclinical advances in bioengineering and regenerative medicine have not yet been translated into effective clinical therapies. The spinal cord's poor regenerative capacity makes repairing damaged and lost neurons a critical treatment step. Reprogramming-based neuronal transdifferentiation has recently shown great potential in repair and plasticity, as it can convert mature somatic cells into functional neurons for spinal cord injury repair in vitro and in vivo, effectively halting the progression of spinal cord injury and promoting functional improvement. However, the mechanisms of the neuronal transdifferentiation and the induced neuronal subtypes are not yet well understood. This review analyzes the mechanisms of resident cellular transdifferentiation based on a review of the relevant recent literature, describes different molecular approaches to obtain different neuronal subtypes, discusses the current challenges and improvement methods, and provides new ideas for exploring therapeutic approaches for spinal cord injury.